Venus Caelestis na monerach Julii Soemias-problemy interpretacji w kontekście kistorycznym - Smyk, Anita (Instytut Historyczny Uniwersytetu Wrocławskiego, 2024)
This article concerns the coins of Julia Soaemias, the niece of Julia Domna and mother of Emperor Elagabalus, on the reverse of which the goddess Venus is depicted. The paper discusses the iconography and ideology of the coins and attempts to determine the role of this Roman goddess with regards to the self-presentation of Julia Soaemias, especially in the context of her son’s religious activities
Keywords: starożytny Rzym; dynastia Sewerów; Julia Soemias; Wenus; mennictwo rzymskie